2001
DOI: 10.1128/iai.69.2.773-778.2001
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Loop 6 of the P2 Porin Protein of Nontypeable Haemophilus influenzae Are Bactericidal against Multiple Strains

Abstract: The P2 porin protein is the most abundant protein in the outer membrane of nontypeable Haemophilus influenzae (NTHI). Analysis of sequences of P2 from different strains reveals the presence of both heterogeneous and conserved surface-exposed loops of the P2 molecule among strains. The present study was undertaken to test the hypothesis that antibodies to a conserved surface-exposed loop are bactericidal for multiple strains of NTHI and could thus form the basis of vaccines to prevent infection due to NTHI. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…Molecular mass heterogeneity also occurs in the corresponding P2 (OmpH) and P5 (OmpA) proteins of Haemophilus influenzae and is also due to differences in the size of hypervariable surface-exposed loop regions (Sikkema & Murphy, 1992;Duim et al, 1997). These surface-exposed loops are thought to interact with the host immune system and, by undergoing antigenic variation, provide the bacterium with an important defence mechanism (Yi & Murphy, 1997;Neary et al, 2001). The observed heterogeneity of the OmpA and OmpH proteins of porcine P. multocida strains might also be due to variation in the size of hypervariable surface-exposed loop regions and might play important roles in the pathogenesis of pneumonic pasteurellosis and PAR.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mass heterogeneity also occurs in the corresponding P2 (OmpH) and P5 (OmpA) proteins of Haemophilus influenzae and is also due to differences in the size of hypervariable surface-exposed loop regions (Sikkema & Murphy, 1992;Duim et al, 1997). These surface-exposed loops are thought to interact with the host immune system and, by undergoing antigenic variation, provide the bacterium with an important defence mechanism (Yi & Murphy, 1997;Neary et al, 2001). The observed heterogeneity of the OmpA and OmpH proteins of porcine P. multocida strains might also be due to variation in the size of hypervariable surface-exposed loop regions and might play important roles in the pathogenesis of pneumonic pasteurellosis and PAR.…”
Section: Discussionmentioning
confidence: 99%
“…Duangkamol Kunthalert, 1 Laura a. Novotny, 2 Helen M. Massa, 3 Glen c. Ulett, 3 Lauren O. Bakaletz, 2 Jennelle M. Kyd 4 and allan W. cripps 3, samples masked any specific responses and thus only rat data are presented. To localize the immunologically important regions within OMP26 in this response, a series of overlapping OMP26 peptides spanning the entire sequence of full-length OMP26 was used as the in vitro proliferation stimulus.…”
Section: Epitope-specific Immune Recognition Of the Nontypeable Haemomentioning
confidence: 99%
“…Several outer membrane proteins (OMPs) of NTHi and its oligosaccharides have been investigated as possible vaccine antigens against NTHi. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] One OMP that has shown promise as a potential vaccine candidate is OMP26. The amino acid sequence of this 26kDa OMP 16 is conserved among NTHi isolates from various disease states.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also demonstrated that a strain-specific immune response to NTHi was directed to epitopes on the loop 5 region of the P2 molecule and was associated with bactericidal activity in animal experiments . Another study also reported the loop 6 of the P2 molecule was capable of inducing bactericidal antibodies (Neary et al 2001). Accumulated evidence from clinical and laboratory investigations by Murphy and coworkers suggest that the P2 molecule is one of surface antigens that participate in strain-specific immune responses in the acute exacerbation of COPD by NTHi Neary et al 2001;Sethi et al 2004).…”
mentioning
confidence: 99%
“…Another study also reported the loop 6 of the P2 molecule was capable of inducing bactericidal antibodies (Neary et al 2001). Accumulated evidence from clinical and laboratory investigations by Murphy and coworkers suggest that the P2 molecule is one of surface antigens that participate in strain-specific immune responses in the acute exacerbation of COPD by NTHi Neary et al 2001;Sethi et al 2004). This study was, therefore, conducted to determine whether repeated airway immunizations with NTHi strains bearing different P2 molecules were capable of inducing protective immunity in lungs against homologous or heterologous strains in a mouse model.…”
mentioning
confidence: 99%